ANALISIS KONSUMSI DAYA MOTOR JENIS BRUSSHES DIRECT CURRENT (BDC) DAN BRUSSHES LESS DIRECT CURRENT (BLDC) PADA KENDARAAN LISTRIK - Achlison, Unang; Teguh Santoso, Joseph; Rozikin, Khoirur; Diapoldo, Fujiama (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
Electric vehicles are starting to be widely used among conventional vehicles. The use of a motor as a driver is a very important component for electric vehicles. The battery current and voltage supplied to the motor will determine the performance of the electric vehicle. Based on the analysis of current and voltage measurement results, it can be concluded that (1) the power requirements using the Brusshes Direct Current (BDC) motor type are greater, (2) Electric vehicles are more efficient when using the Brusshes Less Direct Current (BLDC) motor type.